A study on the major risk factors of stillbirth in the rural areas of Dharwad district: a prospective study - R., Vinolia; Bant, Dattatreya D. (International Journal Of Community Medicine And Public Health, 2018)
Background: As per the WHO recommendation for international comparison, stillbirth is defined as a baby born with no signs of life at or after 28 weeks of gestation. It is estimated that 2.6 million stillbirths occur annually in the world with more than 7300 stillbirths happening every day. More than 2/3rd of these stillbirths are identified to be from the South-east Asian countries and Africa. This study is aimed at obtaining key learning points for future implications. The objectives of the study were to study the risk factors associated with stillbirth and to assess the most common and preventable risk factor(s). Methods: The study was conducted in randomly selected villages of Dharwad district chosen equally from all the taluks of the district. 378 of the registered pregnant women with period of gestation <12 weeks from the selected villages, aged 18 to 35 years were studied. Results: Women with <1 year of birth spacing had higher risk of stillbirth with (X2=242.096 and p<0.05). Women with medical conditions like severe anaemia and hypertension had higher risk of stillbirth (p<0.05). Conclusions: The findings in the study suggest that marital and obstetric factors such as early pregnancies and lack of adequate spacing between pregnancies can have an impact on the normal course of pregnancy leading to adverse events like stillbirth but general factors such as women’s education status do not affect the birth outcome.